Prevalence of Lower Back Pain Among Doctors Working in Jinnah Hospital, Lahore - Raza, Ali; Zulfiqar, Abdullah; Ijaz, Arshia; Rasheed, Hammad; Naseer, Muhammad Bilal; Zahra, Syeda Aiman (International Health Review, 2021)
Doctors are health practitioners responsible for the patients’ overall health and well-being. They are at a remarkably high risk of developing a variety of occupational health conditions as a result of their workplace setting and workload. Among the many conditions of musculoskeletal issues, lower back pain (LBP) is the most prevalent. To determine the prevalence of LBP among doctors. A questionnaire was given to doctors that sought information regarding their social and demographic characteristics, job history, pattern of symptoms, frequency and severity of LBP and factors predisposing to LBP. A total of 97 doctors participated in the study. The prevalence of LBP among doctors was 51.55%. Its prevalence was higher in female doctors as compared to male doctors. Health education regarding appropriate sitting posture and correct lifting techniques can be introduced to reduce the burden of LBP among the affected population.